PARTICIPATION OF GENERAL JURABEK IN JADIDIST MOVEMENTS (TAMADDUN NURI JURNALI, 2025)
This article covers the details of the participation of the son of Major General Zhurabek Qalandar qori in the Enlightenment processes and jadidist movements in Turkestan in the late 19th and early 20th centuries, his meetings with the enlighteners who visited Turkestan.